Cussac Cave (Dordogne, France): The role of the rock support in the parietal art distribution, technical choices, and intentional and unintentional marks on the cave walls. (12th February 2017) - Ferrier, Catherine; Konik, Stéphane; Ballade, Marie; Bourdier, Camille; Chapoulie, Rémy; Feruglio, Valérie; Queffelec, Alain; Jaubert, Jacques
Abstract: In this article, we present the relationships observed between the properties of the rock support in Cussac Cave and the choices made by the Paleolithic artists: the lithology of the limestone and the speleogenesis of the cave resulted in the creation of the vast rock surfaces on which the artists realized monumental engravings. The cartography of the formation processes in the cave and the petrographic analysis of samples collected from the ground show that following a superficial dissolution of the limestone, the rock became softer, thus facilitating engraving, even with a soft tool. The analyses (X-ray Diffraction, X-ray Fluorescence, Raman Spectrometry) indicate a relative concentration of goethite, responsible for the orangish patina visible on the wall surfaces. When engraved, the lighter material under this patina is exposed in the bottom of the incised lines, creating contrasting colors that contribute to the visibility of the depictions. Finally, the alteration of the limestone created a surface that also facilitated the realization of more tenuous marks, such as finger-tracings, as well as involuntary marks made by resting hands.